Una mirada crítica - Londoño Díaz, Wilhelm (Notas de Antropología de las Américas, 2025)
Reseña de libro / Review of the book: Arqueología de la dictadura en Latinoamérica y Europa / Archaeology of Dictatorship in Latin America and Europe. Violencia, resistencia, resiliencia / Violence, resistance, resilience. Editors: Bruno Rosignoli, Carlos Marín Suárez, and Carlos Tejerizo-García. 2020. 278 p. ISBN: 9781407356549